Vernalização e aplicação de ácido giberélico na germinação e desenvolvimento de Penstemon digitalis cv Husker Red - Mello, Anderson Machado de (2008)
Penstemon digitalis cv Husker Red has showy flowers that have the potential to be cultivated as garden flowers as well as cut flowers. Two studies were conducted in Lincoln NE, USA. The first study was carried out to determine if treating plants of Penstemon digitalis cv. Husker Red with gibberellic acid (GA3) and vernalization (cold) periods would produce the best quality cut flowers of penstemon in the shortest possible time, in a repeatable manner. The GA3 concentrations were: 0, 100, 250 and 500 mg L-1 and the vernalization periods were 0, 3, 6, 9 and 12 weeks of cold at 5°C. The experiments were conducted in a greenhouse with plants of Penstemon digitalis cv. Husker Red. There were no significant interactions between GA doses and vernalization periods. The variables: number of days to buds, number of days of plants to flowering and number of days to flowering since buds decreased after GA applications, according to the GA levels and according to the vernalization periods. The variables: plant height, number of flowers per plant and time that flowers lasted on the plants were not affected by GA3 applications neither by different vernalization periods. The second study was conducted to determine if soaking seed with gibberellic acid (GA3) would increase germination of Penstemon digitalis cv. Husker Red seed. The GA3 concentrations were: 0, 10, 50, 100, 200 and 500 mg L-1 (first experiment) 0, 500, 1000 and 1500 (second experiment) and 0, 500 and 1000 (third experiment). The first and second experiments were conducted in a growth chamber while the third experiment was conducted in a growth chamber and greenhouse with seeds either covered or not covered in mix. In all experiments, gibberellic acid increased the percentage and rate of seed germination. The 1000 mg L-1 GA3 was the best treatment. Germination percentage and rate were the highest for seeds grown inside of the growth chamber probably due to the consistency of temperatures and darkness. In the greenhouse, the percentage of seeds that germinated and the rate of germination were similar regardless of whether or not the seeds were covered or uncovered and whether they received either the 500 or 1000 mg L-1 GA3 treatment.